The brain's body : neuroscience and corporeal politics - Pitts-Taylor, Victoria (Duke University Press, 2016)
In The Brain's Body Victoria Pitts-Taylor applies feminist and critical theory to recent developments in neuroscience and new materialist social thought to demonstrate how the brain interacts with and is impacted by power, social structures, and inequality.